Management of controversial gastroenteropancreatic neuroendocrine tumour clinical situations with somatostatin analogues: results of a Delphi questionnaire panel from the NETPraxis program. Issue 1 (December 2016) - Sevilla, Isabel; Segura, Ángel; Capdevila, Jaume; López, Carlos; García-Carbonero, Rocío; Grande, Enrique
Abstract Background There are clinical situations (CS) in which the use of somatostatin analogs (SSAs) in patients with neuroendocrine tumors (NET) is controversial due to lack of evidence. A Delphi study was conducted to develop common treatment guidelines for these CS, based on clinical practice and expert opinion of Spanish oncologists. Methods A scientific committee identified 5 CS with a common core (c-c) [non-functioning NET, not susceptible of surgery/locoregional therapy, Ki67 < 10 % (except for CS5: >10 %), ECOG ≤ 2], and controversy regarding use of SSAs, and prepared a Delphi questionnaire of 48 treatment statements. Statements were rated on a 1 (completely disagree) to 9 (completely agree) scale. Responses were grouped by tertiles: 1–3: Disagreement, 4–6: Neutral, 7–9: Agreement. Consensus was reached when the responses of ≥2/3 participants were located in the same tertile as the median value of all reported responses for that statement. Results Sixty five (81.2 %) of 80 invited oncologists with experience in the management of NETs answered a first round of the questionnaire and 57 (87.7 %) of those 65 answered a second round (mean age 43.5 years; 53.8 % women; median time of experience 9 years). Consensus was obtained in 42 (36 agreement and 6 disagreement) of the 48 statements (87.5 %). RegardingCS1 (Enteropancreatic NET, c-c, non-progressive in the last 3–6 months), overall, SSA treatment is recommended (a wait and see approach is anecdotal and reserved for fragile patients or with low tumor load or ki-67 < 2 %);CS2 (Pancreatic NET, c-c), overall, SSA monotherapy is recommended, except when high tumor load or tumor progression exists, where combination therapy would be considered;CS3 [Gastroenteropancreatic (GEP)-NET, c-c, in treatment with anti-proliferative dose of SSA and progressing], overall, SSA maintenance is recommended at the time of progression, with or without adding molecular targeted drugs;CS4 (GEP-NET, c-c, and negative octreoscan®), SSA in monotherapy is only considered in low-risk patients (low tumor load and Ki-67 < 5 %);CS5 [GEP-NET, c-c (ki67 > 10 %), and positive octreoscan®], monotherapy with SSA is mainly considered in patients with comorbidities. Conclusion Several recommendations regarding use of SSAs in controversial NET CS were reached in consensus and might be considered as treatment guideline.